Electric field profile and breakdown voltage of air gap due to the existence of floating particles - 272904 Mohd. Azhan Mohmed @ Mohamed Zahari; Md. Afendi Md. Piah; Fakulti Kejuruteraan Elektrik (2008)
Project Paper (Sarjana Muda Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2008